Developing an Accident and Emergency HIV Testing Program in Belize City: Recommendations from Key Stakeholders. (19th June 2019) - Wiskel, Tess; Merchant, Roland; Habet, Marta; Mackey, Joy
With the ultimate goal of developing an accident and emergency (A&E) department HIV testing program in Belize City, Belize, we sought input from key stakeholders on program components and potential facilitators and barriers to HIV testing in emergency care. We conducted semistructured interviews among 4 key stakeholder groups at Karl Heusner Memorial Hospital Authority (KHMHA) in Belize City: (1) 20 A&E patients, (2) 5 A&E physicians, (3) 5 A&E nurses, and (4) 5 KHMHA administrators. We performed a qualitative content analysis of the interview transcripts and isolated important themes. Major themes included: (1) Patient selection: patients preferred to test all A&E patients. All other stakeholder groups preferred testing specific patient groups. (2) Training: Specific training should be completed for staff. (3) Confidentiality: integral for testing. (4) Facilitators and barriers: facilitators included respectful relationships, privacy, resources, coordination, and education. Barriers included stigmatization, patient willingness, inadequate resources, privacy, and testing biases.